Design and Analysis of a New Type of Metal Belt Continuously Variable Transmission - Zhang Wu; Guo Wei; Lu Zhengxiong; Cao Jianbo (Jixie chuandong)
The basic structure based on metal belt CVT（ Metal Belt Continuously Variable Transmission,referred to as MB- CVT）,through the introducing the jointless wire rope and changing the metal block shape,a new type of metal belt CVT is designed,namely the Wire Rope- CVT（ WR- CVT）. Through the comparative analysis the constraint condition of two kinds of CVT metal belt ring and wire rope in six degrees freedom,the result shows that the WR- CVT has a stable working state of MB- CVT. The formula of calculating lateral pressure of WR- CVT wire rope and metal block arc groove contact is obtained,the analysis of WR- CVT wire rope and metal block arc groove longitudinal contact and non- contact the relationship of force are carried out,the foundation for the further study of WR- CVT is provided.